(untitled) (Chemical Engineering Research Bulletin, 2023)
Carbon capture systems have been an area of interest since they have the potential to greatly reduce the carbon footprint. Biological carbon capture & utilization systems have the potential to provide better solutions in terms of cost & environmental constraints. In this work, a low-cost pressurized photobioreactor model has been designed and the safety of the pressurized system has been evaluated. Pressurized system is preferable to elevate the carbon capture efficiency. In order to design such a system that can be effective to run in a laboratory setting, several factors have been considered. The results suggest yield strength of the material (60 MPa) is greater than the maximum stress (48.63 MPa) of the system. The photobioreactor houses a composition analyzer at the top & a sparger at the bottom. Stress analysis of the photobioreactor reports a factor of safety of 4.2 and a deformation scale of 1. A hydrodynamic study has been carried out on SolidWorks 2022 to verify the safety of the photobioreactor model in the operation phase. The pressure inside the photobioreactor was found in between 2.69 atm to 2.7 atm for 2 m/s of air velocity at the inlet of the photobioreactor model. The vorticity found was in between 0 to 25.71. Efficient design of large scale industrial photobioreactors may reduce the cost of carbon capture & valorize the process. Chemical Engineering Research Bulletin 23 (2023): 63-68